Keadilan Ekonomi Islam sebagai Solusi Alternatif bagi Krisis Ekonomi Global - Suud Sarim Karimullah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze how Islamic economic principles can be applied effectively in the global economic system. This study uses a library research method with a comprehensive literature analysis with a descriptive and analytical approach. The results state that Islamic economics is a paradigm that offers alternatives and transformative solutions to build a more just, sustainable, and humane global economic system. By integrating the principles of justice, solidarity, and sustainability, Islamic economics can answer the failure of capitalism and socialism in overcoming social inequality, exploitation of natural resources, and financial instability. Through instruments such as zakat, waqf, the prohibition of usury, and partnership-based financing, Islamic economics creates a balance between individual and collective interests while maintaining ecological balance. Challenges in its implementation, such as resistance from the capitalist system, lack of global understanding, and the need for harmonization with modern market mechanisms, require collaborative approaches, technological innovation, and commitment across countries. If implemented consistently, Islamic economics can revolutionize the world's economic structure, create equitable prosperity, and strengthen human relationships with the environment, building the foundation for a more harmonious and sustainable world order.